Migration imaging of the transient electromagnetic method - Li, Xiu; Xue, Guoqiang; Yin, Changchun (Springer ; Science Press, 2017)
This book is based on more than a decade of research the authors have pursued on the pseudo-seismic migration imaging of the transient electromagnetic method, and provides a series of important findings on the theory and applications in this area. It present and analyzes transforming principles, TEM wave field methods, characteristics of the TEM virtual wave field and studies on many significant related technologies. The coverage is supplemented by a wealth of 1-D, 2-D and 3-D figures to illustrate pseudo-seismic theory. The book offers a valuable resource for teachers, students, researchers and engineers in the fields of geophysics, earth exploration and information technology.
Keywords: Electromagnetic fields.; Transients (Electricity); elektronické knihy; electronic books